ANALISIS MANTRA DALAM TRADISI TUANG MINYAK PADA MASYARAKAT MELAYU DUSUN SEMAYONG DESA SUNGAI KUMPAI KABUPATEN SAMBAS TAHUN 2024 - Linda Linda; Hifza Hifza; Nurlisa Nurlisa (CV. ADIBA AISHA AMIRA, 2025)
This study aims to find out and obtain information related to the mantra of the oil pouring tradition in the Sambas Malay community and its relevance to learning Indonesian. This study uses a qualitative approach with a descriptive research type. Data collection techniques use observation, interviews and documentation. The data analysis techniques used are data collection, data reduction, data presentation, and conclusions. The data validity techniques used are source triangulation and member check. The results of the study concluded that: The implementation of the oil pouring tradition is carried out at the age of seven months of pregnancy of the pregnant mother. In addition, the implementation of this oil pouring tradition is also beneficial for the mother and her baby, namely getting safety and smoothness during childbirth. The mantra in the oil pouring tradition of the Malay community has a special meaning, including. Bekasai is interpreted as a term of cleansing, where in this case a person's entire body is smeared with kasai (rice that has been ground), aek tolak balla can be interpreted as a term of request to God to be kept away from various kinds of punishments and kept away from bad luck, pouring oil is interpreted as showing the hope to always remember and maintain the heritage of ancestors, bepapas can be interpreted as asking for protection and cleansing from all forms of evil, bad luck, and disaster, bassi banang means a form of prayer or request to restore or return a person's strength and condition to be stable and strong.